Study on the characteristics of nitrogen dioxide adsorption and storage of coal residue in coal-fired power plants in goaf - Xuefeng Wang (Nature Portfolio, 2021)
Abstract In order to realize the storage of the residual coal in the goaf on the flue gas of the power plant, the adsorption characteristics of nitrogen dioxide in the flue gas of the power plant were studied. The Gaussian09 was used to study the adsorption process of NO2 molecules on coal at the density functional (DFT) B3LYP/6-311G level, and the model of NO2 adsorption by coal was established. Different quantities were obtained using orbital energy changes and molecular bond length changes. According to the principle of molecular adsorption, the adsorption of NO2 by coal is considered to be physical adsorption with endothermic heat. On the basis of simulation, using self-organized experimental devices, the single-component NO2 gas and the simulated coal-fired power plant flue gas were introduced into anthracite, bituminous coal and lignite. In single-component adsorption, the adsorption of NO2 by lignite increases with time. The time to reach equilibrium is related to the properties of the coal itself. In the process of simulated flue gas adsorption, the order of the adsorption amount of coal to flue gas is CO2 > NO2 > N2 > O2. In the simulated flue gas, coal is easy to absorb NO2 and CO2, and the competition between gases reduces the frequency of contact between NO2 and the coal surface. Simulation and experimental results show that coal has obvious adsorption characteristics for NO2, and it is feasible for the residual coal in the goaf to adsorb NO2 in the flue gas of power plants.